REHABILITASI MEDIK PADA SINDROMA DEKONDISI PASCA COVID-19 DERAJAT BERAT - Ivena Ivena; Nelson Sudiyono; Edwin L. Jim; Herdiman T. Pohan (Atma Jaya Catholic University of Indonesia, 2021)
Introduction: COVID-19 is characterized by complaints of fever, cough, weakness, respiratory, and gastrointestinal disorders. The existence of treatment in the isolation room accompanied by prolonged bed rest will cause the patient to experience deconditioning syndrome. Case Report: A man, 58 years old, post severe COVID-19 patients with shortness of breath, ineffective cough and feeling weak in all four extremities due to prolonged bed rest (denconditioning syndrome). Deconditioning syndrome is defined as a reduction in anatomical and physiological function caused by disease, age, or physical inactivity. The patient was given active gradual mobilization, range of movement exercise, endurance, strengthening, balance, and coordination exercise. The patient was also given breathing exercise, chest physical therapy, and effective cough. Seven days after rehabilitation, the patient could regulate his breathing pattern and ambulate independently. The patient was discharged and continue self training at home. Conclusion: Breathing exercise, chest physical therapy, aerobic exercise, muscle strengthening exercises in all four extremities, coordination, balance exercise, and gradual mobilization training are very important in the recovery of post severe COVID-19 patients.